2015
DOI: 10.1007/978-3-319-27261-0_27
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Untangling

Abstract: In this note we show how techniques developed for untangling planar graphs by Bose et al. [Discrete & Computational Geometry 42(4): 570-585 (2009)] and Goaoc et al. [Discrete & Computational Geometry 42(4): 542-569 (2009)] imply new results about some recent graph drawing models. These include column planarity, universal point subsets, and partial simultaneous geometric embeddings (with or without mappings). Some of these results answer open problems posed in previous papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Theorem 1 then implies Corollary 1 since every free collinear set is also a free set. This fact, which implies that v(G) = v(G), has been observed by several authors [5,9,13,15]. To see it, let X = {(x 1 , y 1 ), .…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Theorem 1 then implies Corollary 1 since every free collinear set is also a free set. This fact, which implies that v(G) = v(G), has been observed by several authors [5,9,13,15]. To see it, let X = {(x 1 , y 1 ), .…”
Section: Introductionsupporting
confidence: 55%
“…Corollary 3 is almost tight due to the O( n log 3 n) upper bound for triconnected cubic planar graphs of diameter O(log n) [8]. Corollary 3 cannot be extended to all boundeddegree planar graphs, see [13,20] for reasons why. Da Lozzo et al [9] also proved that planar graphs of treewidth at least k have Ω(k 2 )-size collinear sets.…”
Section: Applications and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be interesting to see whether polynomial area is sufficient. Recently, Dujmović [12] showed that every planar graph has a column planar subset of size at least n/2. No upper bounds other than the one from Theorem 2 are known.…”
Section: Discussionmentioning
confidence: 99%